LOSS OF GLUTATHIONE PEROXIDASE 1 ATTENUATES COLITIS AND IS CRITICAL IN ACTIVATING EPITHELIAL REGENERATIVE RESPONSES. (21st January 2021) - Hendren, Jared; Kasnyik, Koral; Williams, Christopher; Short, Sarah
Abstract: Many selenium-containing "selenoproteins" function as antioxidants, and work by our lab and others has demonstrated that selenoproteins often protect against intestinal inflammatory diseases, including colitis. Glutathione peroxidase 1 (GPx1) is a ubiquitous, mitochondrial and cytosolic selenoprotein which catalyzes the reduction of hydrogen peroxide by glutathione. Previously, we determined that despite its antioxidant role, loss of GPx1 greatly reduced disease severity in the dextran sodium sulfate (DSS) colitis model. Furthermore, GPx1 loss increased baseline intestinal cell proliferation, enhanced enteroid plating efficiency, and induced expression of stem cell-associated genes, such as Lgr5 . Next, we aimed to determine the mechanism by which GPx1 modifies response to DSS. We observed that GPx1 is increased in colonic tissues from DSS-treated mice as compared to nontreated controls, suggesting that GPx1 may functionally contribute to intestinal injury responses. While GPx1 is expressed in both intestinal epithelial and immune cells, in situ hybridization to visualize Gpx1 identified epithelial cells as the most highly expressing cell type, with the greatest Gpx1 upregulation observed in wound-adjacent and regenerative crypts. Next, we investigated whether GPx1 loss affects stem cell function after injury. Here, we determined that both proliferation (p<0.01) and Lgr5 expression (p<0.05) were increased in the crypts of Gpx1 -/ - DSS-treated mice in comparison to WT controls. Similarly, organoids established from ulcerative colitis tissue displayed increased growth rates (p<0.01), expression of stem cell and Wnt target genes such as AXIN2 (p<0.0001) and LGR5 (p<0.01), and proliferation (p<0.05) following GPX1 knockdown. Together, these results indicate that GPx1 has an epithelial-cell autonomous role, and that its loss activates stem cell and proliferative responses which may both protect from intestinal injury and promote healing. Interestingly, recent research has highlighted the role of cellular metabolism in maintaining intestinal stem cell function, and GPx1 has previously been implicated in these processes. RNA-sequencing from DSS-treated mice and gene set enrichment analysis identified a positive association with oxidative phosphorylation-associated genes in Gpx1 -/ - mice (NES: 1.78; FDR q-val: 0.01), suggesting altered metabolism which may favor stem cell function. Further analysis of cellular metabolism using GPX1 knockdown colorectal cancer cells observed higher basal respiration (p<0.0001) and ATP generation (p<0.0001). Together, these results suggest that unlike other intestinal selenoproteins studied to date, loss of GPx1 augments stem cell injury responses to protect against intestinal inflammation, likely via augmenting epithelial regenerative responses.